Q: Simplify the following expression using PEMDAS 4(5 + 3x) – 5( -4 – 2x)

A: 4(5 + 3x) - 5(-4 - 2x) = 20 + 12x - (-20 - 10x) = 20 + 12x + 20 + 10x, we then group like terms together: 40 + 22x. Your final answer is 40 + 22x

Expert answered|LawGradLady|Points 192|

Question

Asked 9/30/2011 9:09:19 PM

Updated 5/31/2014 5:00:03 PM

0 Answers/Comments

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [5/31/2014 5:00:03 PM]

Rating

There are no new answers.

Divide –5 by – 2.5 and multiply the result by – 6.

Question

Not Answered

Updated 9/24/2011 10:25:22 PM

1 Answer/Comment

(-5) / (-2.5) = 2. Now (-6) / 2 = -3

Added 9/24/2011 10:25:22 PM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [2/27/2014 12:52:17 PM]

When 231/385 is reduced to its lowest term we get:

Question

Not Answered

Updated 7/25/2015 4:46:15 AM

1 Answer/Comment

Simplify the following expression using PEMDAS Evaluate: 3xy – 7x When x = 2 and y = -1

Question

Not Answered

Updated 2/27/2014 12:51:04 PM

1 Answer/Comment

3xy – 7x When x = 2 and y = -1

3(2)(-1) - 7(2)

-6 - 14

= -20

3(2)(-1) - 7(2)

-6 - 14

= -20

Added 2/27/2014 12:51:04 PM

This answer has been confirmed as correct and helpful.

Solve: 7x – 11 = 9x – 13 **Weegy:** 7x – 11 = 9x – 13, 7x - 9x = -13 + 11, -2x = -2, x = -2/-2, x = 1 (More)

Question

Expert Answered

Updated 2/1/2014 2:26:16 PM

0 Answers/Comments

how to solve 9( x-2 ) = 8( x+ 1) **Weegy:** 6(x+4)=8(x-2)
6x+ 24 = 8x -16
24+16 = 8x-6x
40 = 2x
40/2 = x
20= x
Answer is x =20
**User:** how to solve -3( x + 2 ) = 18 **Weegy:** D.) { x | x > -3 } **User:** How to solve 4x – 3 + 2x = 8x – 3 – x **Weegy:** 4x – 3 + 2x = 8x – 3 – x
=>2x-3=7x-3 =>3-3=7x-2x =>5x=0 =>x=0/5 =>x=0. **User:** How to solve for x 5x + 4 = 34 **Weegy:** x+5x + 4 = 34 =>6x= 34-4 =>x= 30/6 => x=5 **User:** How to solve for x -9x + 9 = -18 **Weegy:** x -9x + 9 = -18 =>-8x= -18-9 =>x= -27/-8 =>x= 27/8 (More)

Question

Expert Answered

Updated 9/25/2014 10:42:29 PM

4 Answers/Comments

9(x - 2) = 8(x + 1)

9x - 18 = 8x + 8

9x - 8x = 8 + 18

x = 26

9x - 18 = 8x + 8

9x - 8x = 8 + 18

x = 26

Added 9/25/2014 10:38:47 PM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [9/25/2014 10:49:08 PM]

-3(x + 2) = 18

-3x - 6 = 18

-3x = 18 + 6 = 24

x = 24/-3 = -8

-3x - 6 = 18

-3x = 18 + 6 = 24

x = 24/-3 = -8

Added 9/25/2014 10:41:01 PM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [9/25/2014 10:49:18 PM]

5x + 4 = 34

5x = 34 - 4 = 30

x = 30/5 = 6

5x = 34 - 4 = 30

x = 30/5 = 6

Added 9/25/2014 10:41:49 PM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [9/25/2014 10:49:40 PM]

26,996,789 questions answered

There are no comments.